2015
DOI: 10.5194/cp-11-1049-2015
|View full text |Cite
|
Sign up to set email alerts
|

Endless cold: a seasonal reconstruction of temperature and precipitation in the Burgundian Low Countries during the 15th century based on documentary evidence

Abstract: Abstract. This paper applies the methods of historical climatology to present a climate reconstruction for the area of the Burgundian Low Countries during the 15th century. The results are based on documentary evidence that has been handled very carefully, especially with regard to the distinction between contemporary and non-contemporary sources. Approximately 3000 written records derived from about 100 different sources were examined and converted into seasonal seven-degree indices for temperature and precip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 26 publications
0
56
0
Order By: Relevance
“…Summer temperature is represented by seven data series (Büntgen et al, 2006(Büntgen et al, , 2011Camenisch, 2015a;Riemann et al, 2015;Trachsel et al, 2010Trachsel et al, , 2012van Engelen et al, 2001) and winter temperature by five data series (Camenisch, 2015a;de Jong et al, 2013;Glaser and Riemann, 2009;Hasenfratz et al, 2016;van Engelen et al, 2001). Four data series provide information about summer precipitation (Amann et al, 2015;Büntgen et al, 2011;Camenisch, 2015a;Wilson et al, 2013). In a first analysis, the centennial-scale variability is investigated by comparing the temperature mean of the SPM (1421-1550) with the preceding century (1300-1420) and the century afterwards (1550-1700).…”
Section: Reconstructions Of Climate During the Spörer Minimummentioning
confidence: 99%
See 1 more Smart Citation
“…Summer temperature is represented by seven data series (Büntgen et al, 2006(Büntgen et al, , 2011Camenisch, 2015a;Riemann et al, 2015;Trachsel et al, 2010Trachsel et al, , 2012van Engelen et al, 2001) and winter temperature by five data series (Camenisch, 2015a;de Jong et al, 2013;Glaser and Riemann, 2009;Hasenfratz et al, 2016;van Engelen et al, 2001). Four data series provide information about summer precipitation (Amann et al, 2015;Büntgen et al, 2011;Camenisch, 2015a;Wilson et al, 2013). In a first analysis, the centennial-scale variability is investigated by comparing the temperature mean of the SPM (1421-1550) with the preceding century (1300-1420) and the century afterwards (1550-1700).…”
Section: Reconstructions Of Climate During the Spörer Minimummentioning
confidence: 99%
“…Archeomagnetic data Astronomical observations Lake sediments -PMIP3 Community et al, 2015). The remarkable climatic conditions during the 1430s as described in historical documents are marginally mentioned in the literature (Buismann, 2011;Camenisch, 2015b;Fagan, 2002;Lamb, 1982;Le Roy Ladurie, 2004) but have never been assessed in depth. Also the climatic impacts on society and economy have only been examined for isolated areas (Jörg, 2008;Camenisch, 2012Camenisch, , 2015bvan Schaïk, 2013).…”
mentioning
confidence: 99%
“…This shows similar climatic shifts, or weather extremes led to diverging reactions in terms of drift sand stability in different regions. In the Belgian Campine, Camenisch (2015) reported extremely cold winters in the 1430 s and in 1407/1408 AD but these times were characterised by stabilised sand dunes and decreased sand mobility (De Keyzer, 2016). Similarly, the coldest winters and weather extremes during the seventeenth century Maunder Minimum appear to have had no fundamental effect on the Campine dunes (ibid).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, we are not sure that the mentions of plague identified originally by Biraben were in fact plague at all, especially for the medieval period, and as mentioned, we have no way of checking Biraben’s data set without citations to the original manuscripts. This problem is further illuminated by some of the plagues Biraben identified, such as the plague of 1437–1440, which occurred during a period of extreme cold weather ( 35 , 36 ) and manifested as harvest failures and famine-related diseases ( 37 ); research has suggested that waterborne infections were more likely the cause of this pestilence ( 38 ). …”
Section: Biraben Data Setmentioning
confidence: 99%